Ensino e aprendizagem de matemática: o uso de recursos manipulativos em sala de aula - Galdino, Dayana Fonseca [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work, we understand the importance of the use of manipulative resources for learning mathematics. For both we developed a qualitative phenomenological approach. Performing a case study with nine 7th grade students of the Elementary School, we used the abacus of the integers to examine in what way the use of Abacus contributes to students learning. The choice of material was made according to the focus of research, understanding the signs rule. In the analysis and interpretation of data, highlight lines of students, subject of the research, units of meaning that allow us to say that the material using awakened interest in students Who actively participated in the research and enabled them to understand the rule of signs, to operate with integers enabled them to understand the rule of signs, to operate with integers

Neste trabalho temos como objetivo compreender a importância do uso de recursos manipulativos para a aprendizagem matemática. Para tanto desenvolvemos uma pesquisa qualitativa de abordagem fenomenológica. Realizando um estudo de caso com nove alunos do sétimo ano do Ensino Fundamental, utilizamos o ábaco dos inteiros para analisar em que sentido O Uso do Ábaco contribui para a aprendizagem dos alunos. A escolha do material se deu em função do foco da pesquisa, a compreensão da regra de sinais. No procedimento de análise e interpretação dos dados destacamos das falas dos alunos, sujeitos da pesquisa, unidades de significado que nos permitem dizer que o material utilizando despertou interesse nos alunos que participaram ativamente da pesquisa e, possibilitou-lhes a compreensão da regra de sinais, ao operarem com números inteiros
Keywords: Matemática - Estudo e ensino; Ábaco; Ensino - Meios auxiliares; Mathematics Study and teaching